Self-Image and Academic Achievement of Students at the Higher Secondary Level: The Relationship between Self-Image and Academic Achievement at the Higher Secondary Level (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Self-image is simply the subjective angle and for the most part alludes to the totality of an intricate, composed and dynamic arrangement of scholarly convictions, dispositions and suppositions that every individual holds to be valid about his or her own reality. Self-image and accomplishment are progressively intelligent and proportional. It is discovered that specific mental variables like self-image assumes a noteworthy part in deciding the scholastic accomplishment of understudies. Consequently the requirement for this examination. An example of 321 understudies in various classifications of schools following diverse frameworks of training at the higher optional level was picked. The discoveries of the investigation directed uncovered that understudies having a place with focal board schools were better in their self-image and scholarly accomplishment when contrasted with understudies from different sheets. There is likewise a noteworthy and positive connection between self-image and scholastic accomplishment of understudies at the higher optional level.